SEEING AN IMAGE - BEING-IN-THE-WORLD: THE INTERCONNECTIONS BETWEEN VISUALITY, SPATIALITY, AND AGENCY IN PHILOSOPHICAL HERMENEUTICS. - Inishev, Ilya; Biedash, Yuliya (Problems / Problemos, 2013)
The article B dedicated to the revelation of heuristic potential of hermeneutic image conception within discussions on contemporary visual culture. H. G. Gadamer has analysed the image as the visual, spatial and social phenomenon expanding and thereby transforming the accustomed notion of iconic experience. The image is not primarily an object of research for aesthetics and art criticism, but a social phenomenon which has to be considered in its real and imagined character as well as in its interrelations with the lived world structures. By blurring boundaries between art and life in his image theory Gadamer opens up an array of opportunities for the analysis of iconic practices in all their variety: from science to theater.